Effect Of Cinnamomum Zeylanicum Extracts On Growth Of Cell Line Transferred With Bcl-2 - Kasim, Rosmayati (2006)
This study has found that the growth of bcl-2 transfected hybridoma cell line was affected when exposed to various concentrations of cinnamon extracts ranging from 100ug/ml to 600ug/ml. Cells exposure to water extract (100-600ug/ml) led to the reduced in maximun cell number in batch culture. The cells number was reduced immediately when exposed to acetone extract at the concentration around 400ug/ml and 600ug/ml. The cell growth declined when exposed to ethanol extract of cinnamon, as lower as 100ug/ml. Keywords: bcl-2, cinnamon extracts, antioxidants, phenolic compounds